The Role of Strategic Managers in Achieving Competitive Advantage: Formulating Objectives, Vision, Mission, and Company Philosophy for Long-Term Strategy - Farhan, David Nur; Nugroho, Kurniawan Setyo; Febrianto, Satriyadi; Fakhrurazi, M.; Supratikta, Hadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
The Role of Strategic Managers in Achieving Competitive Advantage This research investigates the crucial role of strategic managers in achieving long-term competitive advantage. Competitive advantage is the result of well-planned and implemented strategies, the roots of which lie in the managers' ability to formulate the organization's fundamental elements. Strategic managers function as principal architects who translate the company's aspirations into a cohesive direction for action. The main focus is on the formulation process of objectives, vision, mission, and company philosophy. The vision provides an inspirational outline of the desired future, acting as an emotional anchor and defining the overall direction. The mission clearly defines the purpose of the organization's existence, its scope of operations, and the value it offers to stakeholders. Operational objectives, derived from the vision and mission, provide measurable benchmarks for assessing strategic progress. Meanwhile, the company philosophy (or core values) shapes the organizational culture, guides ethical decision-making, and ensures consistency of actions across all levels. It is found that the clear articulation and effective communication of these elements are paramount. Strategic managers must ensure that each component aligns with one another and with the dynamic external environment. This alignment enables the company to optimally allocate resources, differentiate itself from competitors, and respond agilely to market changes. Thus, the strategic managers' ability to formulate this philosophical and objective foundation directly impacts the company's resilience and profitability over the long term, making them the key drivers in the creation and maintenance of sustainable competitive advantage.